Simulation of Priority Round Robin Scheduling Algorithm - Putra, Tri Dharma; Purnomo, Rakhmat (Sinkron : jurnal dan penelitian teknik informatika, 2022)
In this journal, simulation of priority round robin scheduling algorithm is presented. To imitate the processes of operating system operation, simulation can be used. By simulation, model is used, namely models that represent the characteristics or behaviour of systems. Process scheduling is one important operation in operating system. OS-SIM can be used to model and simulate the operations of process scheduling. Some scheduling algorithms are available in modern operating systems, like First come First Serve (FCFS), Shortest Job First (SJF), Round Robin (RR), Priority Scheduling or combination of these algorithms. One important scheduling algorithm for real-time or embedded system is priority round robin scheduling algorithm. Priority round robin scheduling algorithm is a preemptive algorithm. Each process is given time quantum. Each process has a priority. Here time quantum 3 is given. The higher the time quantum, the more the context switching. By the use of OS-SIM, simulation can be understood easily and thoroughly. The statistics, will be calculated automatically by the system by the simulator, like the number of context switching, average waiting time, average turn around time, and average responds time. With one example, by using quantum=3. The average turn around time is 18.25 ms. The Average Waiting Time is 12 ms. The Average Responds time is 2.75 ms. The total burst time is 25 ms.